Management of vascular perforations that occur during neurointerventional procedures. - Halbach, V V; Higashida, R T; Dowd, C F; Barnwell, S L; Hieshima, G B (American Journal of Neuroradiology, 1991)
This article describes a number of treatment strategies for the management of perforations that occur during neurointerventional procedures. During the past 5 years, we have performed over 1200 endovascular procedures to treat vascular disorders involving the brain and spinal cord (400 cerebral arteriovenous malformations, 230 tumors, 197 carotid cavernous fistulas, 183 aneurysms, 130 dural fistulas, 80 spinal arteriovenous malformations, 18 vein of Galen aneurysms, and 20 cases of vasospasm). Fifteen patients (1.1%) sustained a vascular perforation as a direct result of these procedures. Among these 15 patients, indications for endovascular treatment were six symptomatic arteriovenous malformations, two spinal cord arteriovenous malformations, two cavernous sinus dural fistulas, one transverse sinus fistula, one case of vasospasm following subarachnoid hemorrhage, one direct carotid cavernous fistula, one vein of Galen malformation, and one ruptured basilar artery aneurysm. The vascular perforations were grouped into three probable mechanisms: mechanical perforation of a normal vessel (six patients), mechanical disruption of a dysplastic vessel or aneurysm (five patients), and fluid overinjection (four patients). Treatment of the perforations included immediate reversal of anticoagulants (12 patients) and direct closure of the perforation site with coils (five patients). In addition, closure of the intravascular compartment adjacent to the perforation was achieved with coils (six patients), liquid adhesives (four patients), balloons (two patients), or particles (two patients). In two patients a detachable balloon was placed transiently across the perforation site for several minutes, deflated, and removed when no further extravasation was noted. Five patients were started on anticonvulsant therapy, two of whom have had a new onset seizure related to the perforation.(ABSTRACT TRUNCATED AT 250 WORDS)